Answer:
=−12x+4
Step-by-step explanation:
−6(
−2
/3
+2x)
=(−6)(
−2
/3
+2x)
=(−6)(
−2
/3
)+(−6)(2x)
=4−12x
=−12x+4
The graph is a function because when you use the vertical line test it does not hit more than one point at any given place on the line.
Hope this helped :)
Solving a system of linear equations, we conclude that the measure of side Z is 2√13
<h3>How to find the measure of side Z?</h3>
Remember the Pythagorean theorem. It says that the square of the hypotenuse is equal to the sum of the squares of the legs.
In the image, we can identify 3 right triangles, and with the Pythagorean theorem, we can write a system of 3 equations.
x^2 = y^2 + 4^2
z^2 = y^2 + 9^2
(4 + 9)^2 = z^2 + x^2
We want to solve that for z.
Now, the second equation can be rewritten to:
y^2 = z^2 - 9^2
Now let's replace the first equation into the third one, so we get:
(4 + 9)^2 = z^2 + (y^2 + 4^2)
Now we can replace y^2 by z^2 - 9^2
(4 + 9)^2 = z^2 + ((z^2 - 9^2) + 4^2)
Now we can solve this:
(13)^2 = z^2 + z^2 - 9^2 + 4^2
(13)^2 + 9^2 - 4^2 = 2*z^2
104/2 = z^2
52 = z^2
√52 = z
√(4*13) = z
√4*√13 = z
2√13 = z
We conclude that the measure of side Z is 2√13
If you want to learn more about systems of equations:
brainly.com/question/13729904
#SPJ1
Answer:
#1. X=3 and #2. Y=9
Step-by-step explanation:
Glad i could help, give me a follow, so if you need help with any other question, im here.
Answer:
Suppose that logb b = x.
bx = b (Use the definition of a logarithm.)
bx = b1
x = 1 (Use the common base property.)
So, logb b = 1.